Comparative Analysis of the Implementation of the South Australian Certificate of Education (SACE) Curriculum in Physical Education: Impacts on Student Learning Outcomes in Indonesia and Australia - Bimo Kalbharianto (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2026)
The purpose of the study. This study aims to conduct a comparative analysis of the implementation of the South Australian Certificate of Education (SACE) curriculum in Physical Education (PE/PJOK) between SMA BOPKRI 1 Yogyakarta, Indonesia, and the Adelaide International School (AIS), Australia, and to evaluate its impacts on student learning outcomes. Materials and methods. A convergent mixed-methods design was employed, integrating qualitative and quantitative descriptive approaches. Purposive sampling was used to select Physical Education teachers and students from both institutions. Data were collected through semi-structured interviews, validated questionnaires, direct observation, and document analysis. Quantitative data were analyzed using descriptive statistics and SWOT (Strengths, Weaknesses, Opportunities, Threats) matrix analysis; qualitative data were processed through thematic analysis following the Miles and Huberman model. Results. The SWOT Grand Strategy Matrix positioned SMA BOPKRI 1 Yogyakarta in Quadrant I (Strengths > Weaknesses; Opportunities > Threats), indicating a robust institutional capacity for SACE implementation. EFAS and IFAS scores demonstrated strong organizational alignment (IFAS x-axis: +0.66; EFAS y-axis: +0.60). All three BOSA-AIS program teachers (100%) confirmed successful SACE implementation, and all observed students (100%) reported positive engagement with SACE-based PE learning. Conclusions. The SACE curriculum, when adapted with contextual sensitivity and principal leadership support, effectively enhances student learning outcomes in Physical Education in both the Indonesian and Australian contexts. These findings support the feasibility of international curriculum transfer with structured institutional scaffolding.